Financing green industrial transitions: A comparative analysis of implementation effectiveness in four emerging economies - Anthony Bartzokas (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2026)
Emerging economies confront unprecedented challenges mobilizing finance for green industrial transitions while maintaining development trajectories. This paper examines implementation effectiveness across India, South Africa, Brazil, and Indonesia-major economies representing diverse political systems, economic structures, and policy approaches- documenting systematic gaps between stated climate commitments and realized outcomes ranging from 33% to 77% of stated targets. Through comparative analysis of policy frameworks, financing architectures, and sectoral dynamics spanning renewable energy, industrial decarbonization, sustainable agriculture, and just transitions, we reveal that aggregate capital availability constitutes only partial explanation. Firm-level financial constraints systematically structure which technologies firms can adopt constrained firms pursue incrementally cleaner but emission-intensive options, while only unconstrained firms access frontier low-emission technologies. This "pecking order" mechanism-predicted by recent theoretical work and validated across four diverse country contexts-generates three fundamental policy challenges. Three critical implications emerge. First, green credit must target frontier technologies precisely, yet such targeting creates politically challenging coverage gaps and exceeds institutional capacity. Second, blended finance exhibits fundamental tension between leverage maximization and genuine additionality. Third, just transition programs systematically underserve workers dependent on constrained firms unable to finance transitions. Looking forward, financing effectiveness will depend increasingly on institutional autonomy rather than merely capital costs: capacity to navigate fragmented global financial architectures, preserve infrastructure control, and maintain policy space as geopolitical competition intensifies and debt burdens rise.
Keywords: O38; L52; O16 G28; Q58; 330; green industrial policy; development finance; blended finance; financial constraints; just transitions; emerging economies